Carbochlorination Reduction Process of Waelz ZnO: Characterization of Resulting ZnO-Based Oxides - Lorena Alcaraz; Belén Sotillo; Paloma Fernández; Félix A. López (Crystals)
Zinc-based oxides are the main products obtained after the Waelz process, a metallurgical method used industrially for the treatment of electric arc furnaces. These oxides have certain impurities in their composition, which can be a disadvantage. Carbochlorination reduction reactions have proven to be useful in eliminating certain impurities (especially Pb) through thermal treatments. In this work, a method for purifying Waelz oxide through carbochlorination reduction reactions is presented. Several experiments have been conducted with the aim of obtaining samples with potential end applications. A deep characterization of the purified oxides has been performed by means of X-ray microanalysis, X-ray diffraction, Raman spectroscopy, and cathodoluminescence. These measurements indicate the presence of ZnO and ZnFe2O4 in different proportions, depending on the different amounts of reducing and chlorinating agents used.